Chloroplast genomes of five Oedogonium species: genome structure, phylogenetic analysis and adaptive evolution - Xiong, Qian; Hu, Yuxin; Lv, Wenqi; Wang, Qinghua; Liu, Guoxiang; Hu, Zhengyu (BMC genomics, 2021)
The order Oedogoniales within the single family Oedogoniaceae comprised of three genera, Oedogonium, Oedocladium, and Bulbochaete based on traditional morphological criteria. While several molecular phylogenetic studies have suggested that both Oedogonium and Oedocladium may not be monophyletic, broader taxon sampling and large amounts of molecular data acquisition could help to resolve the phylogeny and evolutionary problems of this order. This study determined five chloroplast (cp) genomes of Oedogonium species and aimed to provide further information on cp genome for a better understanding of the phylogenetic and evolutionary relationships of the order Oedogoniales. The five Oedogonium cp genomes showed typical quadripartite and circular structures, and were relatively conserved in their structure, gene synteny, and inverted repeats boundaries in general, except for small variation in genome sizes, AT contents, introns, and repeats. Phylogenetic analyses based on 54 cp protein-coding genes examined by maximum likelihood and Bayesian analyses using amino acid and nucleotide datasets indicated that both Oedocladium and Oedogonium are polyphyletic groups. A positively selected gene (psbA) was identified in the two Oedocladium species and the terrestrial Oedogonium species, indicating that terrestrial Oedogoniales taxa may have undergone adaptive evolution to adjust to the difference in light intensity between aquatic and terrestrial habitats. Our results enrich the data on cp genomes of the genus Oedogonium. The availability of these cp genomes can help in understanding the cp genome characteristics and resolve phylogenetic and evolutionary relationships of the order Oedogoniales.